Christopher Marlowe : a Renaissance life - Kuriyama, Constance Brown, 1942- (Ithaca, N.Y. : Cornell University Press, 2002)
"Christopher Marlowe (1564-1593) is portrayed in most accounts of his life by biographers and critics as a mysterious and sensational action figure, a hapless pawn of circumstance, or a pseudonymous cipher. Constance Brown Kuriyama's biography reconstructs the eventful life of a radically innovative playwright who flourished briefly and died violently more than four hundred years ago, yet persists in the romantic imagination even today." "Many discoveries about Marlowe's life have emerged over the past hundred years. The author here supplements these findings with new material, placing the dramatist and poet more precisely in the historical milieu. Kuriyama interprets Marlowe's acts of violence - inexplicable though they may seem - as logical consequences of the circumstances he faced. Experience and temperament both accounted for the characteristically brash way he moved through the world."--Jacket.
A Canterbury tale -- Fetching gentry from the university -- Commencing the M.A.: acquaintances, friends, and connections -- A poet's life in London -- Lord Strange and Thomas Walsingham -- Fortune turns base -- A trim reckoning -- The dead shepherd -- Marlowe lost and found.
Includes bibliographical references (pages 241-249) and index.
Keywords: Marlowe, Christopher, -- 1564-1593.; Dramatists, English -- Early modern, 1500-1700 -- Biography; Marlowe, Christopher, -- 1564-1593; Dramatists, English -- Early modern; Marlowe, Christopher; 1500 - 1700; Biography